Early urban impact on vegetation dynamics: Palaeoecological reconstruction from pollen records at the Dongzhao site, Henan Province, China. (30th June 2019) - Ren, Xiaolin; Mo, Duowen; Storozum, Michael; Lemoine, Ximena; Yu, Yanyan; Gu, Wanfa; Lei, Xingshan; Zhang, Jiaqiang; Lü, Jianqing; Kidder, Tristram R.
Abstract: Archaeologists have focused on the social conditions surrounding the development of urbanism around the world; however, the environmental impact of these ancient cities remains unclear. In this paper, we present palynological data from the early Bronze Age city of Dongzhao, Henan Province, China. Our data indicate that vegetation change and the development of early urban settlements are closely linked, with the advent of urban development significantly accelerating deforestation and altering the composition of local vegetation communities. The pollen record from Dongzhao provides new evidence to support the claim that urban expansion, coupled with a drying climate and the expansion of agriculture, dramatically reconfigured the landscapes of Bronze Age China.